2017
DOI: 10.12691/jfnr-5-7-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aqueous Extract of <i>Dendropanax morbifera</i> Leaf on Sexual Behavior in Male Rats

Abstract: Sexual function in an important of the quality of life and subjective well-being in humans. Successful treatment of sexual dysfunction may improve not only sexual relationships, but also overall quality of life. The objective of this study was to determine the effects of Dendropanax morbifera (DM) Lev. leaf extracts on sexual behavior and testosterone levels in male rats. Three different doses of DM (50, 100, and 200 mg/kg/day) were administered orally for 28 days. On day 28 (final day of the sample treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The enhancement of libido may be due to an increase in the anterior pituitary hormone and serum testoster-one levels, which in turn stimulates sexual behavior (32,33). Recently, we reported that an aqueous DME affected the sexual behavior of male rats (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement of libido may be due to an increase in the anterior pituitary hormone and serum testoster-one levels, which in turn stimulates sexual behavior (32,33). Recently, we reported that an aqueous DME affected the sexual behavior of male rats (17).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that an aqueous extract of D. morbiferus leaves affected the sexual behavior of male rats (17). Based on these results, we evaluated the ameliorating effect of DME on LOH using TM3 Leydig cells and aging male rats as in vitro and in vivo models, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In other research, the crude extracts of D. moribifera leaves seemed to exhibit higher immune activation activities and were used as an immunomodulatory agent [ 59 ]. D. morbifera leaf extracts also appear to be a useful natural resource for the management of sexual function [ 60 ]. Meanwhile, D. moribifera is also used in multi-therapeutic applications.…”
Section: Medicinal Uses and Pharmacological Properties Of mentioning
confidence: 99%